Goldgrund und Perspektive Fra Angelico im Glanz des Quattrocento - Quené, Saskia C. (De Gruyter, 2023)
Monographic study of the gold ground in Italian panel painting. Analyzes the art historiographical use of the term in the 20th century. "Gold ground" and "perspective" are not thought of as oppositional. For example, Fra Angelico is shown to develop strategies for perspective representation from within the gold ground. Notes theological, philosophical, and historico-scientific sources.